(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This scientific article provides complete information about the history of the Abu Mansur al-Motrudi complex. Mainly, the history of the establishment of the complex, the activities of the great people who settled here forever and had their place in the Islamic world are also briefly described. The condition of this region during the Shura era is also revealed. The work done during the years of independence is also reflected in the article.